David Busch's Sony [alpha] a7 III : guide to digital photography - Busch, David D. (Rocky Nook, 2018)
"David Busch's Sony Alpha a7 III Guide to Digital Photography is most comprehensive resource and reference for Sony's affordable 24MP full-frame mirrorless camera. With advanced 693-point phase detect autofocus, 5-axis in-body image stabilization, 10 frames-per-second continuous shooting, and 4K video capture, the a7 III offers enthusiasts a versatile combination of advanced features. This book shows you how to master those capabilities as you explore the world of digital photography and hone your creativity with the a7 III. Filled with detailed how-to steps and full-color illustrations, David Busch's Sony Alpha a7 III Guide to Digital Photography covers every feature of this camera in depth, from taking your first photos through advanced details of setup, exposure, lens selection, lighting, and more, and relates each feature to specific photographic techniques and situations. Also included in Chapter 2 is a handy camera "roadmap," an easy-to-use visual guide to the camera's features and controls. Learn when to use every option and, more importantly, when not to use them, by following the author's recommended settings for each menu entry. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your camera's capabilities, whether you're shooting on the job, as an advanced enthusiast exploring full frame photography for the first time, or are just out for fun. Start building your knowledge and confidence, while bringing your vision to light with the Sony a7 III."--Amazon.com